2019
DOI: 10.3390/nano9050774
|View full text |Cite
|
Sign up to set email alerts
|

CoMn2O4 Catalyst Prepared Using the Sol-Gel Method for the Activation of Peroxymonosulfate and Degradation of UV Filter 2-Phenylbenzimidazole-5-sulfonic Acid (PBSA)

Abstract: In this study, a bimetallic oxide catalyst of cobalt-manganese (CoMn2O4) was synthesized using the sol-gel method, and it was then characterized using a variety of techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) spectroscopy, X-ray photoelectron spectroscopy (XPS), and nitrogen adsorption–desorption isotherms. The obtained novel catalyst, i.e., CoMn2O4, was then used as an activator of peroxymonosulfate (PMS) for the catalytic degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It is widely accepted that SO4 − •and HO are the main oxidative radicals in most PS activation processes. In many radical studies, tert-butyl alcohol (TBA) was reported as the trapping agent of HO, while ethanol (ETA) was used as the trapping agent of SO4 − and HO [45]. As it can be noticed that the addition of TBA (3 M) and ETA (3 M) showed strong inhibitory effects on the SS-600-HCl/PS system for phenol degradation.…”
Section: Mechanism Analysis Of Phenol Degradation By Ss-600-hcl/psmentioning
confidence: 99%
“…It is widely accepted that SO4 − •and HO are the main oxidative radicals in most PS activation processes. In many radical studies, tert-butyl alcohol (TBA) was reported as the trapping agent of HO, while ethanol (ETA) was used as the trapping agent of SO4 − and HO [45]. As it can be noticed that the addition of TBA (3 M) and ETA (3 M) showed strong inhibitory effects on the SS-600-HCl/PS system for phenol degradation.…”
Section: Mechanism Analysis Of Phenol Degradation By Ss-600-hcl/psmentioning
confidence: 99%
“…Transition metal manganites of spinel type are valuable functional materials. In particular, they are of interest as magnetic materials [ 46 , 47 , 48 ], catalysts [ 49 , 50 ], photovoltaic materials [ 51 ], electrode materials [ 52 , 53 ], and materials for negative temperature coefficient thermistors [ 54 ]. Therefore, we carried out the solid-state thermolysis of the obtained compounds 1 – 8 in the air flow in the temperature range of 25–950 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Common activation methods of PMS include photo and thermal methods [ 17 , 18 , 19 ], microwave, transition metal ions, zero-valent iron, etc. [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. However, these methods have been found to have defects such as loss of metal ions, high energy consumption, etc.…”
Section: Introductionmentioning
confidence: 99%